Reduced beta‐cell reserve and pancreatic volume in survivors of childhood acute lymphoblastic leukaemia treated with bone marrow transplantation and total body irradiation. (1st September 2014) - Wei, Christina; Thyagiarajan, Manigandan; Hunt, Linda; Cox, Rachel; Bradley, Karin; Elson, Ruth; Hamilton‐Shield, Julian; Stevens, Michael; Crowne, Elizabeth
Summary Background Impaired glucose tolerance (IGT) and diabetes mellitus (DM) occur more frequently after bone marrow transplantation and total body irradiation (BMT/TBI), but the mechanism is unclear. This study investigates insulin sensitivity, β‐cell reserve and pancreatic volume in adult survivors of childhood acute lymphoblastic leukaemia (ALL). Method Survivors (aged 16–26 years) of ALL treated with BMT/TBI (10–14·4 Gy) Group 1 (n = 20, 10 m) were compared with a chemotherapy‐only Group 2 (n = 28, 11 m). Participants underwent assessments of insulin sensitivity by whole body composite‐insulin‐sensitivity‐index (ISIcomp) from oral glucose tolerance tests (OGTTs); first (AIRarg, AIRg, AUCin10) and second (AUC in second phase) phase insulin responses from arginine‐intravenous glucose tolerance tests; and pancreatic volume by abdominal magnetic resonance imaging (MRI). Data were analysed by odds ratio, Chi‐square or Fisher's exact tests, Student's t‐tests, analysis of covariance (ancova) and Pearson's or partial correlations (5% significance). Results Abnormal OGTTs were documented in Group 1 (DM = 2, IGT = 7). Insulin secretion adjusted for insulin sensitivity was lower in Group 1 than Group 2 as a whole [LogAIRarg (P = 0·008), logAIRg (P = 0·013) and logAUCin10 (P = 0·014)] and after exclusion of those with abnormal glucose tolerance [logAIRarg (P = 0·011), logAIRg (P = 0·007) and logAUCin10 (P = 0·006)]. Group 1 had lower pancreatic volume than Group 2 [52·0 (14·2) vs 72·8 (23·5), P = 0·001] cm3, and results were consistent after adjustment for size by body surface area (P = 0·019). Pancreatic volume correlated with logAIRarg adjusted log ISIcomp (partial correlation = 0·34, P = 0·025). Conclusions Adult survivors of childhood BMT/TBI for ALL demonstrated reduced β‐cell reserve and smaller pancreatic volume, both likely additional aetiological factors, with reduced insulin sensitivity, in their increased risk of diabetes.